EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION DAN NUMBER HEAD TOGETHER TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Novianna Miska Risky; Istiqomah Istiqomah (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of the descriptive study was to determine the tendency of mathematics learning outcomes using the Team Assisted Individualization cooperative learning model and the cooperative learning type Number Head Together. Comparatively to test the effectiveness of the cooperative learning model Team Assisted Individualization type and cooperative learning model Number Number Together towards the mathematics learning outcomes of the fourth grade students of Nanggulan Elementary School. Descriptive results showed that the tendency of mathematics learning outcomes using the Team Assisted Individualization cooperative learning model was high with an average of 12.19 in the interval between 9.91 â‰¤ 12.74 and the tendency of mathematics learning outcomes using type cooperative learning models Head Together numbers are high with an average value of 11.8 at intervals between 9.91 <12.74. The results of the analysis obtained a significance value of 0,000. With a value = 0.05. Thus, there were very significant differences in the mathematics learning outcomes of students who were taught using the Team Assisted Individualization cooperative learning model and the cooperative learning type Number Head Together. By looking at the average learning outcomes using Team Assisted Individualization cooperative learning model 12,19 and those using cooperative learning model Number Head Together type 11,8, the Team Assisted Individualization learning model is more effectively applied in mathematics learning than the Number Head Together learning model.